UMPSA and Pahang State Government Study the Feasibility of Constructing Spur Line for ECRL - Muhammad Hafiz Aswad, Ahmad Kamal (UMPSA, 2023)
KUANTAN, 3 August 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), through the Institute of Civilization and Strategic Studies (ITKAS), is set to conduct a Feasibility Study for the Construction of the Spur Line of the East Coast Rail Link (ECRL) Project in Pahang. The study is a collaboration between UMPSA and the Pahang State Government's Economic Planning Unit (BPEN).